Servers Powered By a 10kW In-rack Proton Exchange Membrane Fuel Cell System - Zhao, Li; Brouwer, Jacob; James, Sean; Siegler, John; Peterson, Eric; Kansal, Aman; Liu, Jie (Proceedings of the ASME 2014 8th International Conference on Energy Sustainability & 12th Fuel Cell Science, Engineering and Technology Conference, 2014)
To improve the reliability and the energy efficiency of datacenters, as well as to reduce infrastructure costs and environmental impacts, we demonstrated and evaluated the use of a 10 kW Proton Exchange Membrane Fuel Cell (PEMFC) stack and system for powering the servers in a data center. In this study, we designed, tested and demonstrated a PEMFC system as a Distributed Generation (DG) prime mover that has high reliability and efficiency for both steady state and dynamic operations. The 10kW PEMFC stack and system was designed to power a server rack and eliminate the power distribution system in the datacenter. The steady state electrical properties such as efficiency and polarization curves were evaluated. The ramp rate and dynamic response of the PEMFC system to server and system dynamics was also characterized and can be used to determine energy storage requirements and develop optimal control strategies to enable the dynamic load following capability.